Hydrogen Cyanide in Comet C/2022 E3 (ZTF) from 3.4 mm Wave Spectra - Juncen Li; Jianchun Shi; Yuehua Ma; Jixian Sun (The Astronomical Journal)
The composition inside a comet nuclear can be detected through the molecular rotational emission lines at millimeter or submillimeter wavelengths. We observed a long-period comet C/2022 E3 (ZTF) using the Purple Mountain Observatory 13.7 m radio telescope at 3.4 mm during mid January and early February in 2023. From the observed spectra, the hydrogen cyanide (HCN)( J = 1–0) spectra lines was detected. The mean production rate of HCN is (8.30 ± 1.14) × 10 ^25 molec. ​s ^−1 in mid January and (3.91 ± 0.84) × 10 ^25 molec. ​​​s ^−1 in early February. we also estimated the upper limit of the production rate of HCO+. We obtained the abundance of HCN relative to water, (0.13 ± 0.02)% in mid January when C/2022 E3 (ZTF) got close to the Sun at 1.11 au, and (0.13 ± 0.03)% in early February at 1.16 au. Our conclusion leans toward E3 being similar to most comets, with the abundance of HCN remaining stable during our two observation periods.